Carbon farming, overestimated negative emissions and the limits to emissions trading in land-use governance: the EU carbon removal certification proposal - Philipp Günther; Beatrice Garske; Katharine Heyl; Felix Ekardt (Environmental Sciences Europe, 2024)
This article conducts a qualitative governance analysis of the European Commission's 2022 proposal for a certification framework for carbon removals (CRCF). It highlights potential challenges and legal implications—with a specific focus on carbon farming. While the European Union (EU) acknowledges carbon farming as an important strategy to offset residual emissions, such carbon removal activities are prone to reversals and models often overestimate their sequestration potential. The CRCF aims to account for these issues, but~the analysis shows that the proposal may, in part, undermine international climate and biodiversity goals set by the Paris Agreement and the Convention on Biological Diversity. Key concerns include its failure to consider the normative hierarchy between emission reductions and removals mandated by EU and international law, the introduction of a temporary removal crediting system, the extensive delegation of powers to the Commission, the possibility that it may incentivise shifting effects, and its lack of alignment with other EU environmental policies. Additionally, the CRCF's failure to restrict the use of carbon credits after certification increases the risk of double claiming of removal activities—and the proposal may open the door for to future integration of carbon removals into the EU's emission trading scheme, which should be avoided for various reasons. As an alternative, member states should consider targeted subsidy schemes and regulatory instruments to navigate these challenges in carbon farming effectively.
Keywords: 320; Carbon farming; Carbon dioxide removal; EU law; Soil carbon; sequestration; International law; Paris Agreement; Convention on Biological Diversity; Climate change; Net-zero emissions